Determining the Annealing Temperature Dependency of Wetting and Mechanical Features on Fe3Si Films - Nattakorn Borwornpornmetee; Chawapon Achirawongwat; Thawichai Traiprom; Bunpot Saekow; Supanit Porntheeraphat; Boonchoat Paosawatyanyong; Tsuyoshi Yoshitake; Nathaporn Promros (My University, 2023)
The impact of thermal annealing under temperature alteration on the wetting and mechanical attributes of Fe3Si films built through facing target sputtering (FTS) is an essential topic for study in order to identify their characteristics under varying temperatures. Consequently, we introduced a thermal annealing process in a vacuum for two hours under varying temperatures of 300, 600, and 900 °C to our Fe3Si films created via FTS. The primary purpose of this current research is to examine the effect of the thermal annealing technique under temperature alteration on the wetting and mechanical traits of Fe3Si films. In this research, Fe3Si films were built onto the Si wafer by FTS and divided for use in thermal annealing under temperature alteration. The structural, morphological, wetting, and mechanical traits of the Fe3Si films under thermal annealing are provided in the present work. Based on our information, this work represents an original study on the change in wetting and mechanical traits of Fe3Si films through thermal annealing under temperature alteration.
Keywords: Copper Interconnects and Reliability